Toward Effective Vocabulary Acquisition in EFL Classrooms: Examining the Effect of Differentiated Learning at the Junior High School Level - St. Nur Aima Fatima; Nurdin Noni; Nur Aeni (Ali Institute of Research and Publication, 2026)
This study examined the effect of the differentiated learning approach on EFL students’ vocabulary acquisition at the junior high school level. Vocabulary is a fundamental component of language learning; however, many EFL students still experience difficulties due to differences in readiness levels, interests, and learning profiles. Although differentiated learning has been widely discussed in previous studies, its empirical implementation in improving vocabulary acquisition in junior high school EFL contexts remains limited. Therefore, this study aimed to determine whether the differentiated learning approach significantly affects students’ vocabulary acquisition. This study employed a quantitative method using a quasi-experimental design with a non-equivalent control group. The population consisted of all ninth-grade students at UPT SMPN 3 Kelara, and the sample was selected through purposive sampling, involving two classes as the experimental and control groups. Data were collected through pre-tests and post-tests, and analyzed using statistical tests to measure the differences between groups. The findings revealed that the experimental group demonstrated significantly greater improvement compared to the control group. The mean score of the experimental group increased substantially from 30.71 in the pre-test to 65.95 in the post-test, indicating the effectiveness of differentiated learning in enhancing students’ vocabulary acquisition. In conclusion, the differentiated learning approach significantly improves EFL students’ vocabulary acquisition and provides an effective alternative to conventional teaching methods in promoting student-centered learning at the junior high school level.